Revisiting Stem Cell-Based Clinical Trials for Ischemic Stroke - He, Joy Q.; Sussman, Eric S.; Steinberg, Gary K. (Frontiers in Aging Neuroscience, 2020)
Stroke is the leading cause of serious long-term disability, significantly reducing mobility in almost half of affected patients aged 65 years and older. There are currently no proven neurorestorative treatments for chronic stroke. To address the complex problem of restoring function in ischemic brain tissue, stem cell transplantation-based approaches have emerged as promising restorative therapies. Aligning with the major cell types found within ischemic brain, stem cell based clinical trials for ischemic stroke have fallen under three broad cell lineages: hematopoietic, mesenchymal, and neural. In this review, we will discuss the scientific rationale for transplanting cells from each of these lineages and provide an overview of published and ongoing trials using this framework.